2020
DOI: 10.1155/2020/4156258
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Percutaneous Needle Electrolysis in Dancers with Chronic Soleus Injury: A Randomized Clinical Trial

Abstract: Damage to intramuscular tendons is very common in sports injuries, specifically in soleus muscle injuries. This study sought to compare the effects of applying ultrasound- (US-) guided percutaneous needle electrolysis (PNE) in combination with an eccentric exercise program on pain and functionality in dancers with chronic soleus injury, located in the central tendon. Thirty dancers with injured central tendon of the soleus muscle were randomly allocated to a PNE group (n = 10), an eccentric exercise group (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Currently, there is a high interest in studying soleus muscle characteristics due to its importance during sporting activities as well as for a better understanding of its pathological features [ 5 , 6 , 31 , 32 ]. A soleus muscle pathology may be misdiagnosed and underestimated because of its special clinical features and that, in many cases, soleus disturbances do not require athletes to stop training or playing games [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a high interest in studying soleus muscle characteristics due to its importance during sporting activities as well as for a better understanding of its pathological features [ 5 , 6 , 31 , 32 ]. A soleus muscle pathology may be misdiagnosed and underestimated because of its special clinical features and that, in many cases, soleus disturbances do not require athletes to stop training or playing games [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In specific populations, however, appropriate assessment of this muscle is essential, such as in dancers who rely on the FHL for dynamic stability of the foot during movements that require alternation between extreme plantar flexion and dorsiflexion [14]. Dancers are high-performance athletes who are particularly susceptible to lower extremities -specially foot-injuries [15][16][17][18][19]. By demonstrating the reliability of USI of the FHL, this study may offer a novel approach to assess and quantify the injury status of the FHL, as well as providing the image guidance needed for invasive therapies (such as needle insertion) targeting this muscle.…”
Section: Discussionmentioning
confidence: 99%
“…They were divided based on the muscle echogenicity in three groups: Injury Type 1 group, healthy group (Figure 1), Injury Type 1 and Injury Type 2 (Figure 2). As in previous studies [7,24], a central IMT tear in the soleus muscle was identified when patients reported having symptoms for at least six months, and they established a self-rated progressive stiffness value greater than or equal to 4 points during sports exercises or during the soleus stretching, measured using the numeric rating scale (NRS) [25]. The enrollment was carried out in a private clinic specialized in sports injuries.…”
Section: Participantsmentioning
confidence: 99%